Eifelosaurus – The Lonely Lizard - Jens Koppka (Geoconservation Research)
The Triassic reptile Eifelosaurus triadicus is an icon of the Geopark Vulkaneifel and the Natural History Museum of Gerolstein (West Eifel, Rhineland Palatinate, W Germany). We explore the research history, including geoconservation aspects, and summarize current knowledge of Eifelosaurus, the sole fossil of its kind, identified as an early rhynchosaur. We discuss the local geology, stratigraphy and paleontology of the Lower Triassic in the Eifel area, with emphasis on local palaeoenvironmental conditions during deposition of the Buntsandstein. Among those are spectacular finds of numerous lycopods at Lammersdorf, only few kilometers from Oberbettingen, the source of the partial skeleton of Eifelosaurus. The famous fossil is important for local geotourism, with a hiking trail leading to the quarry where the reptile was probably discovered. Eifelosaurus is an important geoeducational topic for school groups, tourists and locals who visit exhibitions in the “Naturkundemuseum” of Gerolstein, participate in programs and guided tours through the museum.